Combinatorics on Words 10th International Conference, WORDS 2015, Kiel, Germany, September 14-17, 2015, Proceedings - Manea, Florin; Nowotka, Dirk.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 10th International Conference on Combinatorics on Words, WORDS 2015, held in Kiel, Germany, in September 2015 under the auspices of the EATCS. The 14 revised full papers presented were carefully reviewed and selected from 22 submissions. The main object in the contributions are words, finite or infinite sequences of symbols over a finite alphabet. The papers reflect both theoretical contributions related to combinatorial, algebraic, and algorithmic aspects of words, as well as to contributions presenting applications of the theory of words in other field of computer science, linguistics, biology, bioinformatics, or physics.
Keywords: Computer science; Software engineering; Computers; Mathematical logic; Computer science -- Mathematics; Artificial intelligence; Computer Science; Mathematical Logic and Formal Languages; Theory of Computation; Discrete Mathematics in Computer Science; Artificial Intelligence (incl. Robotics).; Software Engineering; Electronic books